The impact of autophagy on peripheral synapses in health and disease - Rudolf, Rüdiger; Khan, Muzamil Majid; Wild, Franziska; Hashemolhosseini, Said (Frontiers in bioscience. Landmark, 2016)
Alterations of autophagy have been linked to several peripheral nervous system diseases, such as amyotrophic lateral sclerosis and Charcot-Marie-Tooth disease. Modulation of autophagy by metabolic or pharmacological interventions has been increasingly recognized as a strategy to fight many of these disorders. Cellular processes that are aberrant in case of impaired autophagy and that might lead to these diseases belong to three different categories: (1) clearing of protein aggregates, (2) regulation of vesicle and cargo turnover, and (3) disposal of damaged mitochondria. This review summarizes the present literature that addresses both, the impact and mechanisms of autophagy on the health of the peripheral nervous system and treatment proposals for human disorders associated with impaired autophagy.
Gesehen am 19.09.2019